Analisis Perencanaan Pengadaan Bahan Baku pada Produksi List Gypsum dengan Pendekatan Lot Sizing - Ardiansyah, Fredy Pri; Khoiroh, Siti Muhimatul (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This study discusses the analysis of raw material procurement planning in the production process of gypsum molding at UD Jaya Gypsum using a lot sizing technique approach. The main problem faced by the company is the inaccuracy in the quantity and timing of raw material orders, which affects production continuity and cost efficiency. This study employs the Economic Order Quantity (EOQ), Lot for Lot (LFL), Period Order Quantity (POQ), Least Unit Cost (LUC), and Least Total Cost (LTC) methods to determine the most optimal order size. Raw material requirement data are obtained from historical demand and production schedules. The results of the analysis show differences in total costs among the methods and provide recommendations for the most efficient lot size ordering for the company. By applying an appropriate lot sizing method, the company can minimize inventory costs while maintaining production continuity.